Imagens de Marighella: o cineasta militante, a diretora-sobrinha, o mesmo herói - Fernando Seliprandy (IdeAs)
This paper proposes a comparative analysis of two documentaries about the same historical character from Brazil: Marighella: retrato falado do guerrilheiro (Silvio Tendler, Brazil, 2001) and Marighella (Isa Grinspum Ferraz, Brazil, 2011). The aim is to discuss the nuances and parallels between the regards of the militant filmmaker and the niece to the biography of Carlos Marighella, the guerrilla leader murdered by the dictatorship in 1969. The theoretical background is the “subjective turn” of documentary film in the last years, the change from an epic and assertive cinema to a more intimate, reflexive cinema. The hypothesis is that, nevertheless the supposed generational or cinematographic affiliations of the filmmaker, the analogies between the two works are noticeable, mainly concerning three issues: the use of the interview-oriented documentary conventions; the coincidence of the plots of the biographic narrative; the celebratory approach to the memory of the guerrilla hero. Despite appearances, the “subjective turn” does not set the films apart. The film-makers’ generations are together in the construction of a consolidated memory of the resistance hero. But only by the careful filmic analysis one can see the epic behind the intimate appearance, and the formula behind an image of novelty.